An Analysis of the Distribution of Carla Cosmetic Products in Accordance with Law No. 33 of 2014 on Halal Product Assurance - Sy, Syifa Qarira; Hanapi, Agustin; Wahyuni, Yenny Sri (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
The growth of the cosmetics industry in Indonesia has led to an increasing demand for innovative and safe products, particularly among Muslim consumers. According to Law No. 33 of 2014 on Halal Product Assurance (UU JPH), all products that are imported, distributed, and traded in Indonesia are required to obtain halal certification. However, this study identifies that several cosmetic products are still available on the market without such certification, including brands such as Carla. This research employs a qualitative empirical–juridical method through interviews and observations involving business actors, shop owners, and consumers. The findings reveal that Carla products are distributed through a consignment system in offline stores and marketed via e-commerce platforms such as Shopee and TikTok Shop. The absence of halal certification is primarily attributed to financial constraints, limited knowledge among business actors regarding certification procedures, and insufficient socialization by the government and relevant institutions. In addition, public awareness regarding the halal status of cosmetic products remains low, while shop owners tend to prioritize product availability and price over halal legality. From a legal perspective, this condition contradicts Article 4 of the Halal Product Assurance Law, which mandates halal certification for all traded products, and reflects weak supervision by the Halal Product Assurance Agency (BPJPH). These findings indicate that the effective implementation of the UU JPH cannot rely solely on regulation but must be accompanied by consumer education, facilitation for business actors, and stronger government oversight.